International Competitiveness: is the reduction of wages the solution? - Vaz, Elsa Cristina (2014)
The purpose of this paper is to analyse the effectiveness of the wage reduction in promoting efficiency and the international competitiveness of the Portuguese economy. A static multi-sectoral and single-country general equilibrium model will be used for the Portuguese case using the data from GTAP7 Data Base. The model allows measuring the changes by sectors. The simulations performed show that the reduction of wages in all sectors lead to negative effects on the productivity and the trade balance of the majority of sectors, albeit small. Only the labour intensive sectors depict an improvement of the trade balance.